Modeling Educational Financing for Private Vocational High Schools in Deli Serdang Regency in the Context of Optimizing School's Marginal Contribution - Yulita Triadiarti; La Ane; Jumiadi Jumiadi; Muhammad Abdillah; Nurul Syahrani (Asian Journal of Social and Humanities, 2023)
The purpose of this research is to develop an educational financing model that best suits the needs in optimizing the marginal contribution value of private vocational high schools in Deli Serdang Regency. This study employs a qualitative research method. The author develops an educational financing model for vocational high schools using a descriptive qualitative method aimed at identifying phenomena occurring in the field to be presented as an educational financing management model. The research was conducted in private vocational high schools in Deli Serdang Regency. In this study, the author selected 31 respondents, including the Head of the Vocational High School Division of the Deli Serdang Education Office, ten Principals, ten Vice Principals for Facilities and Infrastructure, and ten School Treasurers from 13 private vocational high schools. This research produces a Model expected to be effective and efficient in financing private vocational high school education in Deli Serdang Regency. The resulting Educational Financing Model can serve as a standard for implementing school management, especially for private vocational high schools